DISTURBANCES OF LIPID METABOLISM - P. F. Litvitskii ("Paediatrician" Publishers LLC, 2012)
The article contains modern data on etiology, pathogenesis, manifestations and mechanisms of development of the most common forms of lipid metabolism disturbances in humans, such as obesity, emaciation, lipodystrophy, lipidosis, dyslipoproteinemia and atherosclerosis. The authors give the informative materials for self-testing and correction of the knowledge level.